Bagian Biomedis Fakultas Kedokteran Gigi, Universitas Jember Jember, Indonesia - I Dewa Ayu Ratna Dewanti (Journal of Dentomaxillofacial Science, 2011)
Neem is one of the traditional medicine known by society as immunomodulator. On the other hand, 80% of oralinfection diseases is caused by C. albicans. This research is aimed to explain the phagocytosis activities on wistarrats which were inoculated with C. albicans and fed with neem leaves. There are 5 groups, namely control group(KO)with no treatment, the other treatment groups were classified into 4 groups. First group (KP1)was inoculatedwith C. albicans only. KP2 was fed with 50 mg/day/kg BW aqueous extracts from neem leaves, then inoculated withC. albicans start from day 8-21. KP3 was fed with 100 mg/day/kg BW aqueous extract from neem leaves, theninoculated with C. albicans start from day 8-21. KP4 was fed with 200 mg/day/kg BW aqueous extract from neemleaves, then inoculated with C. albicans start from day 8-21. On day 22, the tongue was swabbed for each group,then cut for immunohistochemistry preparation. The study that there was significant difference showed that therewere different results computed using anova, HSD test, and linier regression. The conclusion was neem leavesincreased the phagocytosis activity of wistar rats, inoculated with C.albicans.